1998
DOI: 10.1097/00042560-199808010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Picobirnavirus in HIV-Infected Patients With Diarrhea in Argentina

Abstract: Diarrhea due to enteric pathogens is an important complication of advanced HIV infection. Picobirnaviruses are agents recently linked with human enteritis. In total, 197 fecal samples collected from HIV-infected and noninfected patients with and without diarrhea were investigated for the presence of rotavirus and picobirnavirus by polyacrylamide gel electrophoresis. Picobirnavirus was detected in 8.8% of 57 HIV-infected patients with diarrhea, but it was detected in neither those without diarrhea (p<.018) nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…The primary objective of these environmental studies was to evaluate PBV as an indicator of fecal contamination, the potential health risk of the presence of PBVs in sewages and natural water resources should not be neglected and this finding deserves further investigations. Studies in immuncompromised and immunosuppressed hosts indicated that these viruses might be 'opportunistic pathogens' [38,39,41,42,44,75,80].…”
Section: Discovery Of Picobirnavirusmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary objective of these environmental studies was to evaluate PBV as an indicator of fecal contamination, the potential health risk of the presence of PBVs in sewages and natural water resources should not be neglected and this finding deserves further investigations. Studies in immuncompromised and immunosuppressed hosts indicated that these viruses might be 'opportunistic pathogens' [38,39,41,42,44,75,80].…”
Section: Discovery Of Picobirnavirusmentioning
confidence: 99%
“…Thus, the probable role of PBV as either a primary diarrhoeal agent in immunocompetent children [6,7], a potential pathogen in immunocompromised individuals [38,39,44] or an innocuous virus in the intestine remains elusive and needs to be investigated despite the numerous reports of the presence of PBV in fecal samples of various hosts species; our current knowledge of their biology, etiology, pathogenicity or their transmission characteristics remains subtle [15,32,33,57], mainly because of their non-cultivable status (in vivo and in vitro) that is, the absence of a cell culture system and suitable animal model for propagating the virus. Further studies in gnotobiotic animals may shed light on PBV pathogenic potential [15].…”
Section: Discovery Of Picobirnavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…PBVs have been frequently detected as coinfections together with rotaviruses, caliciviruses and astroviruses (Bányai et al, 2003;Bhattacharya et al, 2006aBhattacharya et al, , b, 2007Rosen et al, 2000). In addition, the higher detection rates of PBVs in immuncompromised patients without the detection of conventional enteric pathogens (Giordano et al, 1998(Giordano et al, , 1999Gonzalez et al, 1998;Grohmann et al, 1993;Martinez et al, 2003) suggest that PBV might be an opportunistic pathogen.…”
mentioning
confidence: 99%
“…In this respect, in these patients emerging viral enteric pathogens (i.e., picobirnaviruses, astroviruses, and caliciviruses) are more frequently associated with diarrhea than either "classic viruses" or bacterial and parasitic enteropathogens (9,19). However, causal association between unusual viral pathogens and gastroenteric syndromes in HIV-infected patients is controversial (9,14). Furthermore, prolonged viral excretion in the absence of gastroenteric symptoms has been reported in immunodeficient patients, including HIV infected (3,6,15).…”
mentioning
confidence: 99%